Parents' Influence on Retirement Planning in Malaysia - Mansori, Shaheen (American Association of Family and Consumer Sciences, 2017)
Many studies have indicated that the development of children's behavior is strongly influenced by their parents’ behavior during childhood. This paper applied the theory of planned behavior as a basis for the analysis of data from a sample of 520 Malaysians aged 18 and over. Regression analysis was used to assess the relationship between parents’ financial behavior and their children's retirement planning. Results showed that: (a) parents play a significant role as agents of financial socialization for their children's retirement planning behavior, and (b) saving attitude mediates this relationship. Suggestions for policymakers and future research are presented.